2001
DOI: 10.1002/polb.10026
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive and mechanical properties of soft nanocomposites: Model studies with blended latex films

Abstract: ABSTRACT:We used a unique approach based on contact mechanics to quantify the adhesive and linear viscoelastic properties of latex films approximately 100 m thick. The latex films were formed from a mixture of two particle types and form stable films consisting of rigid and compliant regions. We used atomic force microscopy to verify that these regions remained well dispersed on the length scale of the original particle size. The properties of the films were determined by h , the volume fraction of the stiffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Fabbroni et al [25] studied the adhesive and mechanical properties of hardsoft nanocomposites. The nanocomposites were made from blends of two different latexes, a latex of small particle size (55 nm) and low T g (soft), and another of large particle size (268 nm) and high T g (hard).…”
Section: Introductionmentioning
confidence: 99%
“…Fabbroni et al [25] studied the adhesive and mechanical properties of hardsoft nanocomposites. The nanocomposites were made from blends of two different latexes, a latex of small particle size (55 nm) and low T g (soft), and another of large particle size (268 nm) and high T g (hard).…”
Section: Introductionmentioning
confidence: 99%
“…However, while some of these works mention the potential to correlate the nano-adhesion of model PSAs to their 'bulk' tack, and peel and shear strengths, no direct comparisons to these specific metrics have been made [59][60][61]. In fact, most other nano-adhesion studies of PSAs also focus solely on their properties at the nanoscale [38,62,63] or compare them to other bulk properties such as the rheological behaviour of the latex [64]. Furthermore, Phillips et al [61] reported the only other account where, to our knowledge, nanoparticle reinforced latexes were investigated using nano-adhesion measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Small-Strain Oscillatory Test. The linear viscoelastic properties of the adhesive layer were obtained by applying a sinusoidal displacement to the adhesive layer and measuring the resultant load: 11,12,32 t sin( )…”
Section: ■ Introductionmentioning
confidence: 99%